Gangguan Fungsi Oral pada Bayi dan Penanganan Awal - Supraptidjuari Soerais Supraptidjuari Soerais (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1985)
Symptoms such as difficulty in feeding during the early life of a baby that might be caused by oral dysfunction will influence the physical, emotional, and social growth and development of the child. The reasons for oral dysfunction in infancy include prematurity, dysmaturity, mental retardation, or brain dysfunction_ An understanding of the mechanism of mature oral function and of normal oral function in infancy is necessary as a basis for the evaluation and treatment of babies with feeding problems. Physiotherapeutic management in cases of babies of age-range from 5 to 67 days with difficulty in feeding due to different causes has been presented. Key Words: oral dysfunction - infancy - feeding problems - growth and development - physiotherapy